2002
DOI: 10.1890/1051-0761(2002)012[0655:amsrpu]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Multi-Species Recovery Plans Under the Endangered Species Act

Abstract: The U.S. Fish and Wildlife Service (USFWS) is relying increasingly on a multi‐species, rather than the more traditional single‐species, approach to recovery planning under the U.S. Endangered Species Act (ESA). Supporters of the multi‐species approach note potential efficiency gains in terms of biodiversity protection and agency resources. By the end of 1998, >55% of all ESA‐listed species with recovery plans were covered within multi‐species plans. A recent analysis found that species within multi‐species pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…Of plans developed since 2000, 73 percent were multispecies plans, compared with 55 percent of the plans developed in previous years. The reason for the lesser effectiveness of multispecies plans is unclear, but it has been attributed to a lack of management focus and consequent lack of sufficient attention to each species' needs (Clark and Harvey 2002).…”
Section: Finding 1: Listing Enhances Recovery Over Timementioning
confidence: 99%
“…Of plans developed since 2000, 73 percent were multispecies plans, compared with 55 percent of the plans developed in previous years. The reason for the lesser effectiveness of multispecies plans is unclear, but it has been attributed to a lack of management focus and consequent lack of sufficient attention to each species' needs (Clark and Harvey 2002).…”
Section: Finding 1: Listing Enhances Recovery Over Timementioning
confidence: 99%
“…This is an important finding given previous studies that have found no difference between overall outcomes of single-and multi-species management (Clark andHarvey 2002, Cullen et al 2005). Moreover, while the predominant focus of conservation planning is on singlethreat mitigation, such as reserve acquisition to stop habitat loss (e.g.…”
Section: Multiple-action Strategy For Multiple Species Is Better Thansupporting
confidence: 63%
“…One explanation for previous lack of support for multi-species and multi-action threat management is the tendency to 'lump' species together based on their habitat use in the same or similar region (Dobson et al 1997), rather than grouping them according to vulnerability to specific threats. In this study, we explicitly grouped species based on their common threats as well as their co-location, and in doing so, focus management on eliminating or mitigating those threats as recommended for successful multi-species management (Clark and Harvey 2002).…”
Section: Multiple-action Strategy For Multiple Species Is Better Thanmentioning
confidence: 99%
“…Fish and Wildlife Service 2013. However, criticisms have arisen suggesting that multispecies conservation planning efforts do not result in better outcomes for listed species (Clark and Harvey 2002). The increasing use of conservation approaches, such as habitat conservation plans and ecosystem management, that take into account whole assemblages of native flora and fauna, as well as abiotic, economic, and social factors, are therefore better suited to dealing with the complexity of conserving biological diversity (Pipkin 1996, Zipkin et al 2010.…”
Section: Discussionmentioning
confidence: 99%